2022
DOI: 10.3390/v14051060
|View full text |Cite
|
Sign up to set email alerts
|

Are Hamsters a Suitable Model for Evaluating the Immunogenicity of RBD-Based Anti-COVID-19 Subunit Vaccines?

Abstract: Currently, SARS-CoV-2 spike receptor-binding-domain (RBD)-based vaccines are considered one of the most effective weapons against COVID-19. During the first step of assessing vaccine immunogenicity, a mouse model is often used. In this paper, we tested the use of five experimental animals (mice, hamsters, rabbits, ferrets, and chickens) for RBD immunogenicity assessments. The humoral immune response was evaluated by ELISA and virus-neutralization assays. The data obtained show hamsters to be the least suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Recombinant S protein or its parts (including RBD, S1, S2, trimerized RBD, full length spike ectodomain, etc.) have been evaluated as candidate vaccines in different animal models, at different concentrations, different schedules and formulated with different adjuvants (53)(54)(55)(56)(57)(58)(59)(60). Beyond experimental differences, in all cases the results obtained show that the different versions of S protein have immunostimulatory capacity to some degree.…”
mentioning
confidence: 99%
“…Recombinant S protein or its parts (including RBD, S1, S2, trimerized RBD, full length spike ectodomain, etc.) have been evaluated as candidate vaccines in different animal models, at different concentrations, different schedules and formulated with different adjuvants (53)(54)(55)(56)(57)(58)(59)(60). Beyond experimental differences, in all cases the results obtained show that the different versions of S protein have immunostimulatory capacity to some degree.…”
mentioning
confidence: 99%
“…These results are in partial disagreement with those by Merkuleva and colleagues who evaluated the immune response induced by a trimeric uncoupled RBD based candidate vaccine expressed in mammalian cells in different animal models. They showed a dose dependent virus VN antibody response in the hamster model, that however proved to be inferior to responses found in other animal models 39 . In our hands coupling of the SARS-CoV-2 RBD to a nanoparticle proved to be crucial for the induction of high titre VN antibodies and protection, as we have shown previously for a MERS-CoV candidate vaccine in different animal species 13 .…”
Section: Discussionmentioning
confidence: 68%
“…Using a similar AH-adjuvanted pre-fusion stabilized (S-2P) we found high neutralizing antibody responses 42 days after a single immunization in mice ( 34 ) and previous studies have demonstrated that the HexaPro antigen adjuvanted with AH elicits robust neutralizing antibody responses in mice when using a standard vaccine regimen (two doses given three weeks apart and evaluation of responses two weeks later) ( 49 ). In contrast, more recent studies have demonstrated that alum adjuvanted recombinant spike or RBD-based vaccines are poor at inducing neutralizing antibody responses, particularly in Syrian hamsters ( 50 , 51 ). In the present study, AH-adjuvanted spike protein was poor at inducing neutralizing antibody responses in Syrian hamsters, regardless of whether the vaccine was administered in an accelerated schedule (10 days apart) or a standard schedule (21 days apart).…”
Section: Discussionmentioning
confidence: 94%